2015
DOI: 10.5901/mjss.2015.v6n2s1p75
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of Undergraduates on the Use of Electronic Examination in a Nigerian University

Abstract: The study investigated opinions of university undergraduates on the use of electronic examination (e-exams

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“… 31 and Bandele et al. 32 who reported that students expressed a more positive attitude towards online exams. Similar findings were also observed by Martin et al.…”
Section: Discussionmentioning
confidence: 96%
“… 31 and Bandele et al. 32 who reported that students expressed a more positive attitude towards online exams. Similar findings were also observed by Martin et al.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown that medical students have shown keen interest and have positive experience using online assessments for both formative and summative assessments [9,[19][20][21]. Elzainy et al stated that majority of the faculty in their study appreciated the tremendous…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been done on electronic examination system. Bandele et al [8] suggested that colleges should accept electronic examinations; expand programs for quality examinations and valid examination results; offer sufficient human and material resources to operate electronic examinations effectively; and make undergraduates able to obtain proficiency in computer and operation of electronic examinations for desirable success of the system. Osang [9] applied electronic examination system in college teaching in Nigeria, and results show that 81.9% of lecturers are proficient in computer, while the remaining 28.4% is being accustomed to the use of basic computer skills.…”
Section: Introductionmentioning
confidence: 99%